Gender and education - Vimala Ramachandran,Ed; Kameshwari Jandhyala,Ed (Readings on the economy, polity and society, 2019)
while the last century has seen a considerable shift in the status of women in Indian society, gender equality in education continues to be influenced by three sets of issues: economy, society and culture; accessibility/availability of formal education; and gender norms. Socio-economic inequalities, connectivity, and cultural beliefs and practices, including a continued preference for sons across the country, play an important role in determining whether girls are given access to both primary and higher Educatio